Generation Mechanism for Interlinked Flux Tubes on the Magnetopause. Issue 2 (26th February 2018) - Farinas Perez, G.; Cardoso, F. R.; Sibeck, D.; Gonzalez, W. D.; Facskó, G.; Coxon, J. C.; Pembroke, A. D.
Abstract: We use a global magnetohydrodynamics simulation to analyze transient magnetic reconnection processes at the magnetopause. The solar wind conditions have been kept constant, and an interplanetary magnetic field with large duskward B Y and southward B Z components has been imposed. Five flux transfer events (FTEs) with clear bipolar magnetic field signatures have been observed. We observed a peculiar structure defined as interlinked flux tubes (IFTs) in the first and fourth FTE, which had very different generation mechanisms. The first FTE originates as an IFTs and remains with this configuration until its final moment. However, the fourth FTE develops as a classical flux rope but changes its 3‐D magnetic configuration to that of IFTs. This work studies the mechanism for generating IFTs. The growth of the resistive tearing instability has been identified as the cause for the first IFTs formation. We believe that the instability has been triggered by the accumulation of interplanetary magnetic field at the subsolar point where the grid resolution is very high. The evidence shows that two new reconnection lines form northward and southward of the subsolar region. The IFTs have been generated with all the classical signatures of a single flux rope. The other IFTs detected in the fourth FTE developed as a result of magnetic reconnection inside its complex and twisted magnetic fields, which leads to a change in the magnetic configuration from a flux rope of twisted magnetic field lines to IFTs. Key Points: Interlinked flux tubes and FTEs were observed in a three‐dimensional MHD simulation The interlinked flux tubes exhibit the same typical signatures of a flux rope; topology analysis shows that it is not a flux rope The interlinked flux tubes are generated due to accumulation of IMF and the formation of multiple magnetic reconnection lines